Numerical Study of Discharge-Head Relationship of Piano Key Weirs for Low Heads - Abhash A.; Pandey K.K. (My University, 2025)
Abstract: Piano Key Weirs (PKW) is a free-flowing weir, and an improvement over the labyrinth weir family. PKW has higher discharge for the same head as compared to other types of weirs. They tend to reduce the upstream submergence in reservoirs or other flow systems and can be effectively used for flood risk mitigation. CFD studies have been carried out earlier but mostly for H/P (Total head to height ratio) greater than 0.1. The present paper investigates the use and validation of Computational Fluid Dynamics (CFD) for modeling Open Channel flows over common hydraulic structures such as PKW for small discharges with the entire range of head to height ratio h/P from 0.035 to 0.1, where h is not the total head upstream of PKW but the head measured at the crest of PKW. The numerical results have been validated with experimental results. Since the discharge is minimal surface tension force has been incorporated in the numerical model. The numerical model is a half PKW unit model with the same geometrical parameters as the experimental setup from Literature. The results show that CFD simulations can reproduce flow depths near PKW with reasonably good accuracy. The present paper compares the head obtained from CFD with that of empirical formula in the Literature but with head measured at the crest of PKW. Investigation of water surface profile and velocity profile near the upstream of PKW has also been carried out. © 2021, Pleiades Publishing, Ltd.